3. Quo Vadis the Contemporary Music Criticism? (The First International Workshop of Journalism in Kalv, Sweden. Reflection, Orientation, Persuasion) - Duţică Luminiţa (Sciendo, 2020)
Annually, in Kalv is organized one of Sweden's most innovative festivals for Contemporary Music. For the first time, on 8-11 August 2019 took place a workshop in Music Journalism field. In this study we intend to show working methods used in Western Journalism and the impact of current music on the cultural level Kalv's rural population. Together with the mentor Andreas Engström from Berlin, we attended concerts, seminars, we interviewed more artists and musicians across the globe, also we wrote different texts, essays and chronicles for publication. To conclude, organising a Musical Journalism Workshop during a festival of contemporary music is a commendable initiative which plays a major role in getting acquainted and gaining a better understanding of the compositional intentions of present-day creators. We will be happy to come back here, in a world at once picturesque and post-modern owing to these unforgettable musical encounters.